Realising Linguistic, Cultural and Educational Rights Through Non-Territorial Autonomy
XVII, 194 p. 9 illus., 5 illus. in color.
Keywords: This open access book assesses Non-Territorial Autonomy (NTA) in terms of its practical capacity to support the linguistic, cultural, and educational rights of national minority groups across Europe. The fact that 2023 marks the 25th anniversary of the coming into force of the Council of Europe Framework Convention on National Minorities (FCNM) and European Charter for Regional and Minority languages (ECRML) makes this book especially timely and relevant. Its numerous detailed empirical studies, one of which uses FCNM reporting as a benchmark, give a picture of the extent (or otherwise) to which international minority rights standards are actually being realized through various NTA arrangements. In keeping with the principles laid out in these foundational documents, the contributions to this volume acknowledge that when it comes to the effective delivery of linguistic, cultural and educational rights, NTA is best regarded not as an alternative but as a complement to territorially based arrangements. David Smith holds the Alec Nove Chair in Russian and East European Studies at the University of Glasgow, UK. Ivan Dodovski is Professor in Critical Theory, and Dean of the School of Political Science at University American College Skopje, North Macedonia. Flavia Ghencea holds the Fundamental Institutions of Administrative Law Chair at the Faculty of Law and Administrative Sciences at Ovidius University of Constanta, Romania.